From Anxiety to Well-Being: A Systematic Review on Mathematics Well-Being and Hidden Math Anxiety in Learning Contexts - Jelita Anastasia Simbolon; Idat Muqodas; Juntika Nurihsan; Mubiar Agustin; Erlin Yuliana; Queen Sheyla Shereen (Jurnal Pendidikan Progresif, 2026)
Many students feel discomfort in mathematics caused by hidden mathematical anxiety. This emotional state is often subtle yet persistent, slowly undermining their self-confidence, perseverance, and willingness to actively participate in mathematical tasks. Although researchers’ focus on the concept of mathematical well-being persists, the direct relationship between concealed mathematical anxiety and students’ emotional experiences in learning remains insufficiently explored in depth. This study aims to investigate how hidden mathematical anxiety affects mathematical well-being and to identify educational and psychological practices that can enhance students’ emotional experiences in mathematics lessons. A systematic review was conducted by collecting articles published between 2013 and 2025 from four databases: Springer, ERIC, Scopus, and SAGE. Of the 165 articles identified in the initial stage, 144 were re-screened against predefined inclusion criteria, and 48 were ultimately included in the final thematic synthesis. Five main themes were successfully identified and analyzed. The research findings indicate that mathematics wellbeing (MWB) has a strong reciprocal relationship with hidden math anxiety, whereby high MWB is associated with low levels of hidden anxiety and more positive engagement in learning. Intrapersonal factors such as self-efficacy, a growth mindset, and emotional regulation play a significant role in enhancing students’ MWB whilst reducing anxiety. Furthermore, a supportive classroom environment and positive teacher-student relationships were found to strengthen mathematical wellbeing. Various psycho-educational interventions, including mindfulness, project-based learning, and gamification, were also effective in balancing academic challenges with emotional comfort, thereby supporting sustained improvement in MWB. Fostering mathematical well-being helps students manage hidden anxiety, strengthen emotional stability, and maintain engagement in the mathematics learning process. A mutually supportive and nurturing learning environment is the primary foundation for realizing this process. Keywords: hidden math anxiety, learning, math anxiety, mathematics well-being, well-being.